Enhanced Pomegranate‐Structured SnO2 Electrocatalysts for the Electrochemical CO2 Reduction to Formate. Issue 6 (15th February 2023) - Daele, Kevin Van; Arenas‐Esteban, Daniel; Choukroun, Daniel; Hoekx, Saskia; Rossen, Alana; Daems, Nick; Pant, Deepak; Bals, Sara; Breugelmans, Tom
Abstract: Although most state‐of‐the‐art Sn‐based electrocatalysts yield promising results in terms of selectivity and catalyst activity, their stability remains insufficient to date. Here, we demonstrate the successful application of the recently developed pomegranate‐structured SnO2 (Pom. SnO2 ) and SnO2 @C (Pom. SnO2 @C) nanocomposite electrocatalysts for the efficient electrochemical conversion of CO2 to formate. With an initial selectivity of 83 and 86 % towards formate and an operating potential of −0.72 V and −0.64 V vs. RHE, respectively, these pomegranate SnO2 electrocatalysts are able to compete with most of the current state‐of‐the‐art Sn‐based electrocatalysts in terms of activity and selectivity. Given the importance of electrocatalyst stability, long‐term experiments (24 h) were performed and a temporary loss in selectivity for the Pom. SnO2 @C electrocatalyst was largely restored to its initial selectivity upon drying and exposure to air. Of all the used (24 h) electrocatalysts, the pomegranate SnO2 @C had the highest selectivity over a time period of one hour, reaching an average recovered Faradaic efficiency (FE) of 85 %, while the commercial SnO2 and bare pomegranate SnO2 electrocatalysts reached an average of 79 and 80 % FE towards formate, respectively. Furthermore, the pomegranate structure of Pom. SnO2 @C was largely preserved due to the presence of the heterogeneous carbon shell, which acts as a protective layer, physically inhibiting particle segregation/pulverisation and agglomeration. Abstract : Pomegranate‐structured SnO2 and SnO2 @C nanocomposite electrocatalysts, with a selectivity above 80 % for the electrochemical CO2 reduction towards formate, are used to highlight the promising possibilities of a particle confinement strategy to enhance electrocatalytic stability for future electrocatalyst design.